(Х+58)-37=91 69-(у-28)=13 Х+58=91+37 у-28=69-13 Х+58=128 у-28=56 Х=128-58 у=55+28 Х=70 у=83 (70+58)-37=91 69-(83-28)=13 91=91 13=13 321+(х+13)=450 204-(х+29)=100 Х+13=450-321 х+29=204-100 Х+13=129 х+29=104 Х=129-13 х=104-29 Х=116 х=75 321+(116+13)=450 204-(75+29)=100 450=450 100=100 (Х-23)×14=56 205÷(у-27)=41 Х-23=56÷14 у-27=205÷41 Х-23=4 у-27=5 Х=4+23 у=5+27 Х=27 у=32 (27-23)×14=56 205÷(32-27)=41 56=56 41=41 89×(b+13)=7120 b+13=7120÷89 b+13=80 b=80-13 b=67 89×(67+13)=7120 7120=7120
(у+9)(у-2)+(3-у)(6+5у)
у=-1/2
(-1/2+9)((-1/2)-2)+(3-(-1/2)(6+5(-1/2)= -9
Пошаговое объяснение:
- 1/ 2 + 9 = 9 - 1 /2 = 9·2 2 - 1 /2 = 18 /2 - 1/ 2 = 18 - 1/ 2 = 17/ 2 = 8·2 + 1 /2 = 8 1 /2 = 8.5
- 1 /2 - 2 = -2 1 /2 = -2.5
3 - (- 1 /2 ) = 3 + 1/ 2 = 3 + 1/ 2 = 3 1/ 2 = 3.5
5×(- 1 /2 ) = -5× 1/ 2 = - 5·1 /2 = - 5 /2 = - 2·2 + 1 /2 = -2 1 /2 = -2.5
8 1 2 ×(-2 1 /2 ) = -8 1 /2 ×2 1/2 = - 1 + 8·2 /2 × 1 + 2·2 /2 = - 17 2 × 5 /2 = - 17·5/ 2·2 = - 85 /4 = - 21·4 + 1 /4 = -21 1 /4 = -21.25
6 + (-2/ 1 2 ) = 6 - 2 / 1 2 = 6 - 2 - 1 /2 = 4 - 1 2 = 4·2 2 - 1 2 = 8 2 - 1 2 = 8 - 1 2 = 7 2 = 3·2 + 1 2 = 3 / 1 2 = 3.5
3 1 2 ×3 1 2 = 1 + 3·2 2 × 1 + 3·2 2 = 7 2 × 7 2 = 7·7 2·2 = 49 4 = 12·4 + 1 4 = 12 1 4 = 12.25
-21 1 4 + 12 1 4 = 12 1 4 - 21 1 4 = 1 + 12·4 4 - 1 + 21·4 4 = 49 4 - 85 4 = 49 - 85 4 = - 36 4 = - 9 · 4 4 = - 9 = -9